Heritability in neuromuscular coordination: implications for motor control strategies - Missitzi, J.; Geladas, N.; Klissouras, V. (Medicine & Science in Sports & Exercise, 2004)
PURPOSE: The aim of this study was to assess the relative power of genetic and environmental contribution to the variation observed in neuromuscular coordination. METHODS: Using the twin model and comparing intrapair differences between monozygotic (MZ) and dizygotic (DZ) twins, we derived heritability estimates (h2). Forty healthy male twins, 10 MZ and 10 DZ pairs, aged 21.5 +/- 2.4 and 21 +/- 2.1 yr, respectively, performed a series of elbow flexions in one degree of freedom with different velocities attempting to accurately reach a target. Neuromuscular coordination was evaluated for both accuracy and economy of movement and assessed by kinematics and EMG activity. RESULTS: The heritability in movement accuracy as assessed by the displacement from the target at 70% maximal velocity was 0.87. The accuracy at 30% and 50% of maximal velocity showed that the intrapair variation of MZ twins did not differ significantly from that of DZ twins. High heritability indexes of 0.85 and 0.73 were found for neuromuscular coordination as expressed by movement economy, assessed by the relative EMG activity of biceps long head at 70% and 50% of maximal velocity; no genetic dependence was found for low velocities. CONCLUSION: In this study, heredity accounted for most of the existing differences in neuromuscular coordination in fast movements. This implies that movement strategies, which are organized in the CNS and control fast movements, are also strongly genetically dependent.